Universities, Politics and Development in Northern Ontario and Northern Sweden: A Comparative Analysis - Weller, Geoffery R.; Rosehart, Robert G. (Canadian Journal of Higher Education, 1985)
Both Ontario and Sweden established universities in their northern regions in the nineteen sixties. This article begins by noting that the two regions are similar in very many ways and that the pressures exerted in both for the establishment of postsecondary educational institutions were much the same. The article continues by comparing the rationales and principles upon which the two sets of universities were founded. It is indicated that while the principle of regional access dominated in northern Ontario the principle of regional service dominated in northern Sweden. Thus the northern Ontario universities began as small, basically undergraduate Arts and Science institutions while the universities in northern Sweden began as specialized professional institutes intended to solve specific regional problems and disparities. The article goes on to analyse the academic, financial and geographic problems faced by the two sets of northern universities since they were founded and the developments that have taken place. An assessment is then made of the successes andfailures of the two systems and it is argued that although some convergence has taken place the Swedish approach has been the more successful of the two.